Confined Interfacial Synthesis of Highly Crystalline and Ultrathin Graphdiyne Films and Their Applications for N2 Fixation. Issue 35 (29th May 2020) - Kan, Xiaonan; Wang, Danbo; Pan, Qingyan; Wang, Yannan; Xiao, Yao; Liu, Jian; Zhao, Yingjie; Li, Zhibo
Abstract: Graphdiyne (GDY), as a new carbon allotrope, possessing both sp‐ and sp 2 ‐hybridized carbon atoms, has attracted extensive attention due to great application potentials in various fields. To realize a fundamental understanding of the intrinsic properties of GDY, the controllable synthesis of ultrathin and highly crystalline GDY is necessary and challenging. Herein, a confined interfacial synthetic strategy towards highly crystalline ultrathin GDY at the water/oil/organogel interface, with greatly improved control over GDY structures, is reported. The morphology and chemical composition of GDY was characterized accordingly. After loading with gold, the as‐prepared hydrophobic Au/GDY system showed excellent performance in the nitrogen reduction reaction, reaching the highest yield of 4.15 μg cm −2  h −1 with a Faraday efficiency of 1.95 %. Abstract : Synthesis in small spaces : Fabrication of an ultrathin, highly crystalline graphdiyne (GDY) film is of vital importance for studies on its intrinsic properties. A liquid/liquid/gel system is successfully applied for the confined synthesis of high‐quality GDY film in a controllable way. After loading with gold, the Au/GDY material shows excellent performance in the nitrogen reduction reaction.